Factors Affecting Real Earnings Management: Additional Evidence of Infrastructure Sector : Factors Affecting Real Earnings Management: Additional Evidence of Infrastructure Sector - Feri, Annisa; Rusmanah, Enok; Sunarta, Ketut (Jurnal Riset Mahasiswa Akuntansi, 2025)
The objective of this study is to investigate the effect of corporate governance, leverage, and profitability on real earnings management. There is a shifting practice from accrual-based earnings management to real-based earnings management because accrual earnings manipulation is more easily detected by regulatory scrutiny. Therefore, the study provides evidence of factors that affect real earnings management. The analytical method applied in this research is verification with the explanatory survey method. The data was tested with multiple linear regression tests, t-tests, F statistical tests, and coefficient of determination. Partial tests show that corporate governance, as proxied with institutional ownership, and leverage as proxied with Debt to Equity Ratio (DER), have no significant effect on real earnings management. However, profitability as proxied with Return on Assets (ROA) significantly affects real earnings management. A simultaneous test shows that overall corporate governance, leverage, and profitability do not affect real earnings management.